the THE EFFECT OF DIFFERENT GROWING MEDIA ON THE GROWTH AND PRODUCTION OF RED GINGER (Zingiber officinale Rosc) - May Br Sitinjak (Agrinula : Jurnal Agroteknologi dan Perkebunan, 2023)
· Introduction: Red Ginger (Zingiber officinale Rosc) is a spice plant that is used as a drink and a mixture of food ingredients. The spicy taste of ginger when drunk gives a sensation as a reliever. Ginger rhizome is also efficacious as a medicine for several diseases such as: arthritis, rheumatism, sprains, muscle aches, coughs, sinusitis, sore throat, diarrhea, colic, cramps, indigestion, loss of appetite, motion sickness, fever, flu, elimination, and infectious diseases. Materials and Methods: This research was carried out in Selayang Village, Finish District, Langkat Regency, North Sumatra, from September 2022 to completion in February 2023. Results: The results showed that the M1 treatment had significant results from almost all observation parameters, namely plant height, number of leaves and fresh weight of rhizomes had a significant effect, except for the parameter of the number of tillers. showed that the highest vegetative growth of red ginger was in treatment M1 (top soil and cow manure) resulting in the highest plant height compared to other treatments. Keywords: Red Ginger, Manure for Cows, Goats, Chickens, NPK.